Inequality, financialization and stagnation - Yılmaz Akyüz (South Centre, 2017)
The failure of exceptional monetary measures pursued in response to the financial crisis in advanced economies to achieve a strong recovery has created a widespread concern that these economies suffer from a chronic demand gap and face the prospect of stagnation. This paper reviews and discusses the alternative views on the causes of the slowdown in accumulation and growth and the policies implemented and proposed to deal with it. It is argued that growing inequality, notably the secular decline in the share of wages and financialization are the main factors. Neither spending booms driven by financial bubbles, nor exporting unemployment through trade provide sustainable solutions. It is necessary to rebalance capital and labour, restrain finance and assign a greater role to the public sector in aggregate demand management and income and wealth distribution. However, the dominant neoliberal ideology rules out such socially progressive and economically effective solutions. Consequently, stagnation is likely to remain the new normal in the years to come with governments attempting to reignite growth by creating credit and asset bubbles and/or trying to export unemployment through beggar-thy-neighbour macroeconomic, labour market, trade and exchange rate policies, thereby generating financial and economic instability and tensions in international economic relations with significant repercussions for emerging and developing economies.
Keywords: 300